Effect of FMD vaccination on various semen quality parameters in Frieswal crossbred bulls - A S SIROHI; N CHAND; S TYAGI; N SRIVASTAVA; A SHARMA; HEMLATA HEMLATA (Indian Journal of Animal Sciences, 2016)
The primary objective of the present study was to assess the semen quality parameters in Frieswal crossbred bulls